Comprehensive Meta-Analysis (CMA) 3.0: a software review - Philipp Brüggemann; Kunjan Rajguru (Journal of Marketing Analytics, 2022)
Comparative analyses of different publications on the same topic are becoming increasingly popular in several areas of marketing research. Especially in research strands with many different empirical studies, there is a strong need for a systematic method to verify the multitude of results. Meta-analysis is such a method to empirically synthesize multiple research results. This software review examines probably the most popular software for the implementation of meta-analyses: Comprehensive Meta-Analysis (CMA) 3.0 ( https://www.meta-analysis.com/ ).
Keywords: 650; Meta-analysis; Comprehensive Meta-Analysis 3.0; CMA 3.0; Software review